Association of CTLA4 Gene Polymorphism with Transfusion Reaction after Infusion of Leukoreduced Blood Component - Wen, Ying-Hao; Lin, Wei-Tzu; Wang, Wei-Ting; Chiueh, Tzong-Shi; Chen, Ding-Ping (Journal of clinical medicine, 2019)
Leukocytes and cytokines in blood units have been known to be involved in febrile non-hemolytic transfusion reaction (FNHTR), and these adverse reactions still occur while using pre-storage leukoreduced blood products. Blood transfusion is similar to transplantation because both implant allogeneic cells or organs into the recipient. CTLA4 gene polymorphism was found to be associated with graft-versus-host disease in hematopoietic stem cell transplantation. We performed a prospective cohort study at a major tertiary care center to investigate the correlation of CTLA4 gene polymorphism and transfusion reactions. Selected CTLA4 gene SNPs were genotyped and compared between patients with transfusion-associated adverse reactions (TAARs) and healthy controls. Nineteen patients and 20 healthy subjects were enrolled. There were 4 SNPs showing differences in allele frequency between patients and controls, and the frequency of “A” allele of rs4553808, “G” allele of rs62182595, “G” allele of rs16840252, and “C” allele of rs5742909 were significantly higher in patients than in controls. Moreover, these alleles also showed significantly higher risk of TAARs (OR = 2.357, 95%CI: 1.584–3.508, p = 0.02; OR = 2.357, 95%CI: 1.584–3.508, p = 0.02; OR = 2.462, 95%CI: 1.619–3.742, p = 0.008; OR = 2.357, 95%CI: 1.584–3.508, p = 0.02; OR = 2.357, 95%CI: 1.584–3.508, p = 0.02, respectively). The present study demonstrated the correlation of CTLA4 gene polymorphism and transfusion reaction, and alleles of 4 CTLA4 SNPs with an increased risk of TAARs were found. It is important to explore the potential immune regulatory mechanism affected by SNPs of costimulatory molecules, and it could predict transfusion reaction occurrence and guide preventive actions.